Glasses in coarse-grained micrometeorites - Varela, Maria Eugenia (2009)
Micrometeorites (MMs, interplanetary dust particles with 25 - 500 μm diameters) carry the main mass of extraterrestrial matter that is captured by Earth. The coarse-grained MMs mainly consist of olivine aggregates, which - as their counterparts in CC chondrites - also contain pyroxenes and glass. We studied clear glasses in four coarse-grained crystalline MMs (10M12, M92-6b, AM9, and Mc7-10), which were collected from the ice at Cap Prudhomme, Antarctica. Previous studies of glasses (e.g., glass inclusions trapped in olivine and clear mesostasis glass) in carbonaceous and ordinary chondrites showed that these phases could keep memory of the physical-chemical conditions to which extraterrestrial matter was exposed. Here we compare the chemical compositions of MM glasses and glasses from CM chondrites with that in experimentally heated objects from the Allende CV chondrite and with glasses from cometary particles. Our results show that MMs were heated to variable degrees (during entry through the terrestrial atmosphere), which caused a range from very little chemical modification of the glass to total melting of the precursor object. Such modifications include dissolution of minerals in the melted glass precursor and some loss of volatile alkali elements. The chemical composition of all precursor glasses in the MMs investigated is not primitive such as glasses in CM and CR chondrite objects. It shows signs of pre-terrestrial chemical modification, e.g., metasomatic enrichments in Na and Fe2+ presumably in the solar nebula. Glasses of MMs heated to very low degree have a chemical composition indistinguishable from that of glasses in comet Wild 2 particles; giving additional evidence that interplanetary dust (e.g., Antarctic MMs) possibly represents samples from comets. © 2009 Elsevier B.V. All rights reserved.